Epigenetic inheritance of cell fates during embryonic development - Cheedipudi, Sirisha; Genolet, Oriana; Dobreva, Gergana D. (Frontiers in Genetics, 2014)
During embryonic development a large number of widely differing and specialized cell types with identical genomes are generated from a single totipotent zygote. Tissue specific transcription factors cooperate with epigenetic modifiers to establish cellular identity in differentiated cells and epigenetic regulatory mechanisms contribute to the maintenance of distinct chromatin states and cell-type specific gene expression patterns, a phenomenon referred to as epigenetic memory. This is accomplished via the stable maintenance of various epigenetic marks through successive rounds of cell division. Preservation of DNA methylation patterns is a well established mechanism of epigenetic memory, but more recently it has become clear that many other epigenetic modifications can also be maintained following DNA replication and cell division. In this review, we present an overview of the current knowledge regarding the role of histone lysine methylation in the establishment and maintenance of stable epigenetic states.